Electron dynamics in the normal state of cuprates: Spectral function, Fermi surface and ARPES data - Zubov, E.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
An influence of the electron–phonon interaction on excitation spectrum and damping in a narrow band electron subsystem of cuprates has been investigated. Within the framework of the t–J model an approach to solving a problem of account of both strong electron correlations and local electron–phonon binding with characteristic Einstein mode ω0 in the normal state has been presented. In approximation Hubbard-I it was found an exact solution for the polaron bands. We established that in the low-dimensional system with a pure kinematic part of Hamiltonian a complicated excitation spectrum is realized. It is determined mainly by peculiarities of the lattice Green’s function. In the definite area of the electron concentration and hopping integrals a correlation gap may be possible on the Fermi level. Also, in specific cases it is observed a doping evolution of the Fermi surface. We found that the strong electron–phonon binding enforces a degree of coherence of electron–polaron excitations near the Fermi level and spectrum along the nodal direction depends on wave vector module weakly. It corresponds to ARPES data. A possible origin of the experimentally observed kink in the nodal direction of cuprates is explained by fine structure of the polaron band to be formed near the mode –ω0.